Integrated Ultra Low Invasion–Nanoparticles Drilling Fluid (ULIN): Drilling Additives with Low Environmental Impact as Innovation to Solve Common Drilling Issues - Sasa Aulia (International Journal of Regional Innovation, 2022)
Drilling issues is extremely costly and a smart additives selection could be one of the ways to cope with these issues. Integrated Ultra Low Invasion–Nanoparticles Drilling Fluid (ULIN) purpose to overcome common drilling problems such as formation instability, differential sticking, lost circulation, and clay swelling by minimizing the invasion through environmentally safe drilling fluid additives. Ultra Low-Invasion produces a thin, deformable, yet robust shield that serves as the foundation for a low-permeability barrier at the formation's face, temporarily sealing pore throats. This seal forms after only a few seconds of invasion and has been demonstrated in laboratory experiments to be exceedingly effective at essentially inhibiting future fluid invasion or pressure transmission. On the other hand, nanoparticles drilling fluid inhibiting shales by either plugging pore in shales, viscosifying water in drilling fluids, and or osmotically dehydrating shales. It has a very high surface area to volume ratio resulting in improved physical and chemical sensitivity, boosting their performance efficiency. ULIN has exceeded the original oil production with an additional 1,800 BOPD produced by 11 wells. It also reduces the formation damage up to 93% from 64.3% to 4.5% in Naricual Formation. ULIN is safe for the environment while it can inhibit the reactive montmorillonite shales, declining rheology dropping back, controlling fluid loss amount and lubricity enhancement. Parameter of the feasibility of establishing a factory using economic analysis with an annual sales of 37,449,000 USD, and ULIN get a profit before tax of 23,108,266.89 USD and a profit after tax of 14,340,733.11 USD with a parameter calculation is a positive NPV, IRR of 40.01% including the cash flow and present value start to be positive in the 3rd year when the system starts operating. ULIN has a payback period of 4.3 years. From the result of the analysis, it can be concluded that ULIN has good prospects and deserves to be implemented.